Reservoir characteristics and dolomitization mechanisms of the third member of the Feixianguan formation: a case study from the Puguang gas field, Sichuan, China - Shengbo YANG; Jian Chen; Yuling ZHANG; Changbing HUANG; Xinyu ZHU; XueQin Zhao (Carbonates and Evaporites, 2026)

Spatially resolved multi-omics analysis of indigenous Bacillus-fortified high-temperature Daqu - Hao Shi; Yuling Shen; Qingqing Ye; Hui Yu; Maoling Tian; Hongmei Wang; Yang Wei; Shiying Yan; Yiping Chen; Jie Zhang; Shu Li; Yang Yang; et al. (Food Research International, 2026)

Modeling the cooling effects of urban rivers on surrounding built-up areas via a SOMUCH-based scaled outdoor experiment - Lin Liu; Xin Feng; Jian Hang; Jiajia Hua; Guanwen Chen; Qing Wu; Na Zhao; Yuguang Zhao; Yuling Yang (Sustainable Cities and Society, 2026)

Small-sample BOD₅ interval prediction for aeration recommendation using conformal calibrated LightTransformer-LGBM model - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Shuang Ren (Journal of Environmental Chemical Engineering, 2026)

Divergent temporal dynamics of yield response to nitrogen fertilization across the three major cereals - Xiaowen Zhao; Meitong Wang; Baiheng Su; Yuling Li; Xiaohe Wang; Yu Jiang; Zhenghui Liu; Ganghua Li; Yanfeng Ding; Weiwei Li (Field Crops Research, 2026)

Environmental Gating of Cerium Species- versus Contact-Associated Toxicity in Rod-Like Cerium Nanomaterials - Yiqing Chen; Jiahui Zhao; Yuling Dong; Kang Zheng; Changjian Xie; Di Cui (Aquatic Toxicology, 2026)

Multi-omics insights into key aroma compound formation during Chinese bayberry wine fermentation by Pichia kluyveri ZFM-0524 - Shuxun Liu; Mingfeng Cao; Yan Zhao; Yufeng Xu; Luan Zhang; Yuling Cai; Qing Gu (International Journal of Food Microbiology, 2026)

Legume dominance and context-dependent benefits of cover crops for nitrogen supply in global agriculture - Xiaowen Zhao; Yuling Li; Meitong Wang; Baiheng Su; Chongxi Wen; Xiaohe Wang; Ganghua Li; Ziting Wang; Yanfeng Ding; Weiwei Li (European Journal of Agronomy, 2026)

Using transgenic zebrafish to assess the effects of SCCPs exposure on embryonic neural development and its potential mechanisms - Jinxian Yang; Ruiyao Huang; Jin Wang; Mengna Jiang; Fengxu Wang; Yuling Jiang; Jiaxin Liu; Mingjing Sun; Sheng Chen; Tian Zhou; Xinyuan Zhao; Shunxing Zhu (Chemico-Biological Interactions, 2026)

Responses of soil quality, enzyme-based ecosystem multifunctionality, and maize yield to short-term straw return with shallow-buried drip irrigation in Northeast China - Chutong Liu; Shucheng Liu; Boyang Hou; Yinong Zhao; Peilong Luo; Jing An; Yuling Zhang (Plant and Soil, 2026)

Cationic Dendrimer-Directed Pore Architecture in Polyamide Membranes for Tunable Ion Separation - Bingbing Yuan; Menghan Wu; Jinmiao Cui; Lei Zhang; Zequn Liao; Ping Hu; Yuling Ren; Lihong Liu; Siheng Zhao; Meng You; Dongxiao Yang; Q. Jason Niu (Water Research, 2026)

Explainable machine learning-based study on the applicability of thermal indicators for university classrooms in summer - Luyao Wang; Fan Fei; Yan Wang; Yongwei Song; Yuling Xiao; Weidong Wu; Kunkun Zhao; Hiroatsu Fukuda (Building and Environment, 2026)

The Identification of Digramma interrupta (Diphyllobothriidae: Ligula) in a Captive Red-Crowned Crane and a Crucian Carp Reveals a New Case for Co-Occurrence - Maolin Lu; Yuling Yang; Mengchao Zhou; Yaxian Lu; Honyan Yu; Ruisi Zhang; Tianlu Liu; Mengru Zhao; Lei Han; Zhijun Hou (Acta Parasitologica, 2026)

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Development and Validation of An HPLC Method for Isolation and Structural Elucidation of Impurities in Chlorogenic Acid Self-Microemulsion Formulations - Yue Gao; Yanan Wang; Jing Xu; Ming Ji; Dongyang Zhao; Yanqi Han; Longhui Hao; Yi Zhang; Ying Sun; Zhenshuai Qin; Jun Ye; Hongliang Wang; et al. (Journal of Pharmaceutical Innovation, 2026)

Plastic film mulch mitigates soil respiration by reducing the duration of freeze-thaw transition - Yufei Li; Kaiping Zhang; Wucheng Zhao; Yuling Li; Ningning Zhang; Pingxing Wan; Zhongke Zhou; Jianjun Yang; Hongyuan Kan; Feng Zhang (Soil and Tillage Research, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Development of a high ethyl hexanoate-producing strain via ARTP mutagenesis and fermentation optimization using agricultural by-products - Yuling Li; Zhiqiang Wang; Renzhi Wan; Xin Zeng; Bingyue Xin; Biao Zhang; Jie Qiao; Deyin Zhao; Mingtao Zhao; Youyu Xie; Zhuangzhuang Jiang; Huawei Zeng; et al. (Biocatalysis and Agricultural Biotechnology, 2026)

A decision support system for coagulant dosage using explainable NSGA-II optimized stacking framework - Wangben Zhao; Yuling Liu; Lu Wang; Shuaishuai Li; Li Sun; Ren Shuang (Journal of Water Process Engineering, 2026)

Multistimuli-responsive degradable metal-organic framework nanoplatform potentiates photoimmunotherapy for hepatocellular carcinoma via cGAS-STING pathway activation - Yahui Wu; Zhipu Liu; Yi Zhang; Senfeng Zhao; Miaoqing Li; Ruiyang Zhang; Jiahui Cao; Peng Liu; Liming Song; Yin Liu; Yunpeng Zhai; Weijie Wang; et al. (Chemical Engineering Journal, 2026)

Effects of stocking density on growth and glucose metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Zhuohang Feng; Shuangyue Luo; Yaxin Wang; Yuling Xu; Kang Dong; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Aquaculture, 2026)

Comammox Nitrospira dominates autotrophic nitrification in paddy fields under long-term fertilization - Bingjie Ren; Yanping Wang; Yuchao Wang; Yuling Yang; Zhenfa Su; Haikun Wu; Wangting Yang; Yuhan Jin; Jinghao Jin; Shuai Liu; Lidong Shen; Xu Zhao (Agriculture, Ecosystems & Environment, 2026)

Interpretable machine learning model based on floc images for monitoring the coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Peng Guo; Chuanchuan Dou; Wangben Zhao (Process Safety and Environmental Protection, 2026)

Physicochemical properties, microbial diversity, metabolites and their potential relationships of traditional Chinese Zhacai fermented for different periods - Xinyi Wang; Yuanli Luo; Yuanqing Gu; Ting Ren; Yuling Liu; Xinhui Wang; Nan Zhao; Xin Nie; Dayu Liu; Zhiping Zhao (International Journal of Food Microbiology, 2026)

Constructing amorphous CoP/Vs-Ni3S2 p-n junction with enhanced interface built-in electric field: A strategy for stable and high-performance overall water splitting catalysis - Zhiwei Liu; Aize Hao; Rongxing He; Niandan Zhao; Yuling Ye; Xiaonan Liu (Chemical Engineering Journal, 2026)

Anticancer Activity of Endophytic Bacterial Extracts from Potentilla supina in HepG2 and HCT116 Cells - Xia Li; Xinxin Zhao; Jinqiu Gui; Yuling Liu; Guiru Kong (Current Microbiology, 2026)

Differences in nighttime radiance across urban residential communities in China - Yi Zhou; Yuling Jin; Gaohui Wen; Xianhui Hu; Hao Zhou; Yuchao Luo; Guohua Zhou; Haile Zhao (Journal of Environmental Management, 2025)

Machine learning-assisted identification of core flavor compounds and prediction of core microorganisms in fermentation grains and pit mud during the fermentation process of strong-flavor Baijiu - Jiang Xie; Jiaxin Hong; Chunsheng Zhang; Xin Yuan; Zhigang Zhao; Dongrui Zhao; Shimin Wang; Baoguo Sun; Ran Ao; Jinyuan Sun; Yuling Sun; Mingquan Huang; et al. (Food Chemistry, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Synthesis of guanylhydrazone functionalized tetraphenylethylene for combating antibiotic resistance and biofilms - Shuwen Guo; Zijun Chen; Yuling He; Haipeng Xu; Yuwei Zhao; Ye Yang; Peng Yang (Chemical Engineering Journal, 2025)

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Analysis of metabolic characteristics of highly resistant grass carp bred on the basis of constitutive expression level of innate immune molecules - Yuling Wei; Bin Li; Zhe Long; Zongjun Du; Zhao Lv; Tiaoyi Xiao (Fish & Shellfish Immunology, 2025)

Long-term plastic film mulching increased maize yield and water use efficiency - Linrong Han; Yuling Li; Jun Zhu; Zhongke Zhou; Wucheng Zhao; Yifan Yang; Wenjuan Zhang; Xuetong Zhang; Feng Zhang (Field Crops Research, 2025)

Assessment of stability differences among various grassland biomes under severe drought in the northern China and Tibetan Plateau - Haile Zhao; Yi Zhou; Xin Chen; Yuan Qi; Yuyang Chang; Yuchao Luo; Xingjie Yin; Yuling Jin; Zhihua Pan; Pingli An (Agriculture, Ecosystems & Environment, 2025)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Novel insights into the morphological effects of trace organic contaminants on water/PhAC selectivity in nanofiltration of sewage - Junhao Zhao; Yanan Wang; Zuqiong Jiang; Yuefei Song; Nan Deng; Yuling Ren; Ronghua Ma; Kai Jiang (Journal of Hazardous Materials, 2025)

Tissue-specific effects of stocking density on fatty acid composition and liver metabolism in rainbow trout (Oncorhynchus mykiss) - Zhao Li; Kang Dong; Yuling Xu; Yaxin Wang; Zhishuai Hou; Qinfeng Gao; Shuanglin Dong (Fish Physiology and Biochemistry, 2025)

Untargeted lipidomic deep-profiling of human plasma via high-performance aza-Prilezhaev aziridination-LC-MS: Unraveling C C isomeric signatures of Charcot-Marie-Tooth disease - Yuling Li; Weiran Zhao; Xiang Xiang; Yunlei Hu; Xiaoqiang Zhang; Wenjian Sun; Xiaoxuan Liu (Analytica Chimica Acta, 2025)

Regulation of coagulant dosage in water treatment based on explainable integrated time-series deep learning models - Wangben Zhao; Yuling Liu; Ren Shuang; Wang Lu; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Process Safety and Environmental Protection, 2025)

Exothermicity analyses and energy efficiency of a novel liquid cooling strategy in suppressing thermal runaway propagation of a lithium-ion battery module - Hanyu Zhao; Xuguang Tang; Lun Li; Junhui Gong; Yuling Xiao (Process Safety and Environmental Protection, 2025)

A copper-doped mesoporous nanoplatform with dual enzyme-mimic activities for amplified cuproptosis and immune response - Qingqing Xu; Shuaipeng Feng; Yue Cao; Yang Li; Zhu Liu; Qiuling Deng; Jiaru Lan; Donghua Di; Yuling Mao; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Molecular Characterization and Antiviral Function Against GCRV of Complement Factor D in Barbel Chub (Squaliobarbus curriculus) - Yu Xiao; Zhao Lv; Yuling Wei; Mengyuan Zhang; Hong Yang; Chao Huang; Tiaoyi Xiao; Yilin Li (Fishes, 2025)
The barbel chub (Squaliobarbus curriculus) exhibits remarkable resistance to grass carp reovirus (GCRV), a devastating pathogen in aquaculture. To reveal the molecular basis of this resistance, we investigated complement factor D (DF)—a rate-limiting serine protease governing alternative complement pathway activation. Molecular cloning revealed that the barbel chub DF (ScDF) gene encodes a 1251-bp cDNA sequence translating into a 250-amino acid protein. Crucially, bioinformatic characterization identified a unique N-glycosylation site at Asn139 in ScDF, representing a structural divergence absent in grass carp (Ctenopharyngodon idella) DF (CiDF). While retaining a conserved Tryp_SPc domain harboring the catalytic triad (His61, Asp109, and Ser204) and substrate-binding residues (Asp198, Ser219, and Gly221), sequence and phylogenetic analyses confirmed ScDF’s evolutionary conservation, displaying 94.4% amino acid identity with CiDF and clustering within the Cyprinidae. Expression profiling revealed constitutive ScDF dominance in the liver, and secondary prominence was observed in the heart. Upon GCRV challenge in S. curriculus kidney (SCK) cells, ScDF transcription surged to a 438-fold increase versus uninfected controls at 6 h post-infection (hpi; p

Ginger exosome-covered mesoporous polydopamine nanoplatform ameliorates liver fibrosis via antioxidation and macrophage phenotypic transformation - Junhong Zhou; Hongwei Xu; Zhu Liu; Yuling Mao; Yian Li; Liwan He; Shuaipeng Feng; Donghua Di; Siling Wang; Qinfu Zhao (Chemical Engineering Journal, 2025)

Identification and characterization of a novel halolysin from Halostella sp. PRR32 with two C-terminal extensions - Yu Jin; Juntao Ke; Yuling Hao; Aodi Zhang; Han Wu; Yue Ding; Shengda Zhao; Jing Han; Aimin Liu; Shaoxing Chen (Extremophiles, 2025)

Characteristic analysis of floc size distribution and image texture evolution in chemical coagulation process - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Process Safety and Environmental Protection, 2025)

Study on water temperature variation trend and disturbance patterns in hydropower development section of the upper Yellow River - Chenxu Zhao; Yuling Liu; Ce Song; Zixuan Yan (Ecohydrology & Hydrobiology, 2025)

Effects of temperature and salinity on CO2 fluxes dynamics and respiration metabolism in the sea cucumber Apostichopus japonicus (Selenka) - Yaoping Mei; Yuling Xu; Qinfeng Gao; Zhao Li; Shuanglin Dong (Marine Pollution Bulletin, 2025)

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Environmental impacts and carbon reduction benefits of mining photovoltaic systems: A case study of Ningdong coal base - Yongliang Zhang; Peixian Li; Ximin Cui; Guorui Wang; Yuling Zhao; Guangyao Zhu (Journal of Cleaner Production, 2025)

Afforestation increases glomalin-related soil protein content and enhances its association with stable soil carbon in karst regions - Lei Xie; Qiumei Ling; Peilei Hu; Yuling Zhang; Wei Zhang; Yuan Zhao; Kelin Wang (Forest Ecology and Management, 2025)

The structural characteristics and expression characteristics of C1S in response to GCRV infection in grass carp - Yuling Wei; Zhao Lv; Zongjun Du; Tiaoyi Xiao (Fish & Shellfish Immunology, 2025)

Exogenous melatonin enhancing the accumulation of flavonoids and carotenoids in wolfberry fruit at cold storage - Rong Jiang; Zhiqiang Wang; Yixin Jia; A. Biao; Yuan Zong; Chao Yang; Minglin Li; Hongjiao Wang; Yuling Zhao; Ying Wang; Shaohua Zeng (Food Research International, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Evaluation of water vapor from CARRA reanalysis based on GNSS and radiosonde observation in the Arctic - Ce Zhang; Shuaimin Wang; Yuling Zhao; Yujing Xu; Jiajia Zhang; Yanhan Mo; Hong Yu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Experimental study on hydrophysical properties and slope planting of ecological composite material solidified loess - Changgen Yan; Jinhui Zhao; Zhuolong Jia; Hengxing Lan; Han Bao; Yuling Shi (Journal of Environmental Management, 2025)

Natural selection of Lacticaseibacillus paracasei mutant: Weaken the post-acidification of fermented milk - Lei Li; Han Lu; Yuling Xue; Yannan He; Baohua Zhao; Lianzhong Ai; Shijie Wang (Food Bioscience, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

Trends in precipitable water vapor in North America based on GNSS observation and ERA5 reanalysis - Yuling Zhao; Ce Zhang; Shuaimin Wang; Yujing Xu; Hong Yu (Climate Dynamics, 2025)

Transcriptomic analysis reveals the mechanism of ozone fumigation combined with polyethylene nanopackaging for delaying the browning and softening of mushrooms (Agaricus bisporus) - Biao Wang; Jianmin Yun; Weihong Guo; Jiawei Shen; Ting Wang; Fengyun Zhao; Yuling Qu; Liang Yao (Postharvest Biology and Technology, 2025)

Effect of mainstream-forced-entrainment control strategy on the combustion performance of a cavity-based combustor - Yuling Zhao; Mingyu Li; Cheng Gong (Fuel, 2025)

Enzymatic browning of button mushrooms during postharvest cold chain circulation - Biao Wang; Ting Wang; Jianmin Yun; Yuling Qu; Xuerui Wang; Fengyun Zhao; Liang Yao (Food Bioscience, 2025)

Hyperbranched polymer wrapped UIO-66-NH2 as covalent intermediate layer to enhance polyamide membrane for Li+/Mg2+ separation and acid/alkaline stability - Bingbing Yuan; Shuang Yuan; Chaozheng Jia; Ping Hu; Siheng Zhao; Yuling Ren; Meng You; Shengchao Zhao; Kuo Chen; Xiaozhuan Zhang; Dongxiao Yang; Juhui Jiang; et al. (Desalination, 2025)

Collagen IV/laminin-1 coated temozolomide-prodrug hydrogel for recruiting and eradicating residual glioma cells - Yufu Zhu; Jiaqi Jin; Yang Lu; Diancheng Hang; Xuefeng Zhang; Gang Zhao; Qing Wang; Yuling Li; Hongmei Liu (Chemical Engineering Journal, 2025)

Temperature sensitivity of soil respiration to elevated temperature and nitrogen availability - Yufei Li; Kaiping Zhang; Yuling Li; Pingxing Wan; Zhongke Zhou; Wucheng Zhao; Ningning Zhang; Ning Chai; Zhixin Li; Yalan Huang; Feng Zhang (Soil and Tillage Research, 2024)

Constructing a visual detection method for coagulation effect based on image feature machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao; Hao Shu (Journal of Water Process Engineering, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

NiCo layered double hydroxide anchored on MXene/tannin carbon cryogel composite with 3D hierarchical sea urchin-like structure for asymmetric supercapacitors - Yuling Lan; Shirui Wang; Zhanhui Yuan; Weigang Zhao (Chemical Engineering Journal, 2024)

The identification of signature genes and their relationship with immune cell infiltration in age-related macular degeneration - Jinquan Chen; Long Zhao; Longbin Zhang; Yiling Luo; Yuling Jiang; Peng H (Molecular Biology Reports, 2024)

Ecological impacts of vermiculite and submerged macrophytes on sediment enzyme activity in lake restoration: Insights from the mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Journal of Water Process Engineering, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Constructing a visual detection model for floc settling velocity using machine learning - Shuaishuai Li; Yuling Liu; Zhixiao Wang; Chuanchuan Dou; Wangben Zhao (Journal of Environmental Management, 2024)

Effects of wheat germ treated with different stabilization methods on dough characteristics and steamed bread quality - Gongqi Zhao; Shiqiang Hu; Qianqian Huang; Yuling Yang; Ligong Zhai; Qian Gao; Liping Yang (Journal of Cereal Science, 2024)

Enhanced generation and effective utilization of H2O2 for simultaneous aging of plastics in the C3N4/Vis-LED system with the addition of phenol - Xiaoman Zhang; Ting Zhang; Hongyang Guo; Shuqi Wan; Xiaodan Liu; Jianhui Sun; Yuling Zhao; Shuying Dong; Xianfa Su; Maohong Fan (Chemical Engineering Journal, 2024)

Active role of iron-dependent AOM in paddy fields under different long-term fertilizer management schemes - Yuling Yang; Lidong Shen; Yuhan Jin; Yanan Bai; Shuwei Wang; Xu Zhao (Science of The Total Environment, 2024)

Changes in compound temperature and precipitation extremes from combined effects of multiple circulation factors over China - Jingpeng Zhang; Tianbao Zhao; Juanjuan Zhang; Yuling Ren; Zhi Li (Journal of Hydrology, 2024)

Combining effects of submerged macrophytes and lanthanum-modified bentonite on sediment enzyme activity: Evidence from mesocosm study - Chenxu Zhao; Yuling Liu; Zixuan Yan; Wangben Zhao; Jiayu Sun (Chemosphere, 2024)

The interplay of soil physicochemical properties, methanogenic diversity, and abundance governs methane production potential in paddy soil subjected to multi-decadal straw incorporation - Yuling Yang; Lidong Shen; Evgenios Agathokleous; Shuwei Wang; Yuhan Jin; Yanan Bai; Wangting Yang; Bingjie Ren; Jinghao Jin; Xu Zhao (Environmental Research, 2024)

Epidemiologic trends and changes in humoral immunity and lymphocyte subsets levels among hospitalized children with Mycoplasma pneumoniae infection during 2019–2023 - Linyan Tang; Kaiwen Zheng; Lanlan Ma; Ling Chen; Yuling Zhao; Li Li; Ke Wang; Jing Zhang; Xing Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The Footprints of Mitochondrial Fission and Apoptosis in Fluoride-Induced Renal Dysfunction - Qiyong Zuo; Lin Lin; Yuling Zhang; Mohammad Mehdi Ommati; Hongwei Wang; Jing Zhao (Biological Trace Element Research, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

MAP kinase MKK: A central regulator in the development, toxigenic potential, and pathogenesis of Penicillium expansum infecting pears - Xifei Chen; Lina Zhao; Yuling Shu; Solairaj Dhanasekaran; Yu Zhang; Yali Zhou; Xiaoyun Zhang; Maoyu Wu; Hongyin Zhang (Postharvest Biology and Technology, 2024)

The role of MASP1 in the complement system and expression characteristics in response to GCRV infection in grass carp - Yuling Wei; Zhao Lv; Tiaoyi Xiao; Zongjun Du (Fish & Shellfish Immunology, 2024)

An aeration requirements calculating method based on BOD5 soft measurement model using deep learning and improved coati optimization algorithm - Wangben Zhao; Yuling Liu; Xing Zhou; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Journal of Water Process Engineering, 2024)

Responses of rice qualities to temperature and light in three different ecological environments in karst regions - Yuling Xia; Jianquan Qin; Ruike Huang; Fan Feng; Quanzhi Zhao; Xiaoyan Song (Journal of Cereal Science, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

New Butterfly-Shaped Naphthalimide-Based AIE Gens: Synthesis and Photophysical Properties - Hui Zhang; Meng Zhou; Yuling Zhao; Tianzhi Yu; Xvyan Xv (Journal of Fluorescence, 2024)

Mapping the dynamics of intensive forage acreage during 2008–2022 in Google Earth Engine using time series Landsat images and a phenology-based algorithm - Haile Zhao; Yi Zhou; Guoliang Zhang; Xin Chen; Yuyang Chang; Yuchao Luo; Yuling Jin; Zhihua Pan; Pingli An (Computers and Electronics in Agriculture, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Neutral pH photoenzymatic activity of Au-doped g-C3N4 nanosheet for colorimetric detection of total antioxidant capacity in food samples - Xianming Li; Wentong Fan; Honghu Tang; Dongdong Li; Yuling Xiao; Bin Yang; Yi Zhao; Peng Wu (Food Chemistry, 2024)

A novel polyethylene nanopackaging combined with ozone fumigation delayed the browning and softening of Agaricus bisporus during postharvest storage - Biao Wang; Jianmin Yun; Chenguang Ye; Siya Xu; Weihong Guo; Fengyun Zhao; Yuling Qu; Yang Bi (Postharvest Biology and Technology, 2024)

Cr and N co-doped biochar driving controllable peroxydisulfate activation pathways to degrade tetracycline: Pyrrolic N inducing singlet oxygen generation - Lijun Guo; Liming Zhao; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2024)

Effects of Dietary Zinc on Growth Performance, Digestive Enzyme Activities, Antioxidant Status, and Immune Responses of Sea Cucumber Apostichopus japonicus - Yuling Xu; Qinfeng Gao; Shuanglin Dong; Zhishuai Hou; Yaoping Mei; Xueqi Li; Kang Dong; Zhao Li (Biological Trace Element Research, 2024)

Assay for transposase accessible-chromatin with high throughput sequencing (ATAC-seq) analysis the molecular responses of postharvest pear during Penicillium expansum infection - Yali Zhou; Lina Zhao; Shuyang Yue; Yuling Shu; Xifei Chen; Solairaj Dhanasekaran; Xiaoyun Zhang; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Association of short-term PM2.5 exposure with airway innate immune response, microbiota and metabolism alterations in human airways - Shuaiqi Zhao; Huijun Li; Fuyun Yang; Yishu Yang; Yuling Zeng; Zhen An; Juan Li; Hui Wu; Jie Song; Weidong Wu (Environmental Pollution, 2024)

The hysteresis damage of cold exposure on tissue and transcript levels in mice - Jing Zhang; Shiwan You; Lan Yu; Yuling Zhang; Zuoping Li; Na Zhao; Bo Zhang; Lihua Kang; Shiguo Sun (Journal of Thermal Biology, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Fabrication and characterization of polyvinyl alcohol/sodium alginate loaded carvacrol/silica hollow microspheres composite hydrogel as a colourimetric freshness indicator - Hongdan Hao; Bingchao Duan; Lidan Zhang; Lan Wang; Lingli Zhang; Yufei Wang; Yuanyuan Li; Chunmei Zhao; Guochao Jia; Yuling Li; Congjun Liu; Kui Lu (Food Bioscience, 2024)

Nanozyme-mediated biocatalysis as a mitochondrial oxidative stress amplifier for tumor nanocatalytic immunotherapy - Junya Lu; Luming Song; Shuaipeng Feng; Kaili Wang; Yuling Mao; Yikun Gao; Qinfu Zhao; Siling Wang (Chemical Engineering Journal, 2024)

The impacts of aridification on land surface phenological changes in the farming-pastoral ecotone of northern China based on the climatic zoning method - Guoliang Zhang; Yuling Jin; Yi Zhou; Xin Chen; Haile Zhao; Sicheng Mao; Yuchao Luo; Siyu Chen; Xiuyue Wu; Zhihua Pan; Pingli An; Peiyi Zhao (Theoretical and Applied Climatology, 2024)

Long-term effectiveness and sustainability of EHC remediation in carbon tetrachloride-contaminated groundwater: Mechanistic understanding and practical applications - Liu Ling; Yaqiang Wei; Haobo Niu; Hang Zhao; Yuling Chen; Dan Qu; Miao Gao; Jian Chen (Journal of Cleaner Production, 2024)

The delaying effect of a novel polyethylene nanopackaging on postharvest stipe elongation of Flammulina velutipes and its mechanism analysis - Yuxuan Zhao; Jianmin Yun; Biao Wang; Yuling Qu; Fengyun Zhao; Yang Bi (Postharvest Biology and Technology, 2023)

Structural comparison and expression function analysis of BF/C2 in Ctenopharyngodon idella and Squaliobarbus curriculus - Yuling Wei; Zhao Lv; Qiaolin Liu; Jianbo Yu; Yu Xiao; Zongjun Du; Tiaoyi Xiao (Fish & Shellfish Immunology, 2023)

Synthesis and Performance of Imide-Based Small Molecules Containing Carbazole Groups with AIE Properties - Haina Wang; Hui Zhang; Tianzhi Yu; Yuling Zhao (Journal of Fluorescence, 2023)

Long-term fertilization enhances the activity of anaerobic oxidation of methane coupled to nitrate reduction and associated microbial abundance in paddy soils - Yuling Yang; Lidong Shen; Xu Zhao; Evgenios Agathokleous; Shuwei Wang; Bingjie Ren; Wangting Yang; Jiaqi Liu; Jinghao Jin; Hechen Huang; Hongsheng Wu (Soil Biology and Biochemistry, 2023)

Immunogenic response of recombinant pseudorabies virus carrying B646L and B602L genes of African swine fever virus in mice - Lishuang Deng; Sirui Gu; Yao Huang; Yuling Wang; Jun Zhao; Mincai Nie; Lei Xu; Siyuan Lai; Yanru Ai; Zhiwen Xu; Ling Zhu (Veterinary Microbiology, 2023)

Land use/cover changes and subsequent water budget imbalance exacerbate soil aridification in the farming-pastoral ecotone of northern China - Guoliang Zhang; Xin Chen; Yi Zhou; Haile Zhao; Yuling Jin; Yuchao Luo; Siyu Chen; Xiuyue Wu; Zhihua Pan; Pingli An (Journal of Hydrology, 2023)

A novel oral biomimetic delivery system enhancing both the mucosal and systemic immunity of influenza virus vaccine - Hongyan Lu; Yikun Gao; Jianmin Chen; Jing Chai; Ansheng Li; Tongtong Sun; Yuling Mao; Ye He; Qinfu Zhao; Jinghai Zhang; Siling Wang (Chemical Engineering Journal, 2023)

hsa_circ_0000417 downregulation suppresses androgen receptor expression and apoptotic signals in human foreskin fibroblasts via sponging miR-6756-5p - Junqiang Huang; Cheng Su; Pingan Lu; Xiangyou Zhao; Yuling Liu; Qike Xie; Chao Chen (Molecular Biology Reports, 2023)

Combustion and emission performance of a trapped-vortex gas turbine combustor fueled by RP-3 kerosene - Qian Wang; Mingyu Li; Yuling Zhao; Jiankun Xiao (Fuel, 2023)

The cotton pectin methyl esterase gene GhPME21 functions in microspore development and fertility in Gossypium hirsutum L. - Yihan Xu; Yanhua Jiang; Junye Jiao; Hongli Zheng; Yuqing Wu; Yuling Li; Rayhangul Abdursul; Yanyan Zhao; Liping Ke; Yuqiang Sun (Plant Molecular Biology, 2023)

Effects of land-use change on carbon emission and its driving factors in Shaanxi Province from 2000 to 2020 - Chenxu Zhao; Yuling Liu; Zixuan Yan (Environmental Science and Pollution Research, 2023)

Chrome shaving-derived biochar as efficient persulfate activator: Ti-induced charge distribution modulation for 1O2 dominated nonradical process - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Science of The Total Environment, 2023)

Large-scale metabolome analysis reveals dynamic changes of metabolites during foxtail millet grain filling - Tao Wang; Lu Xing; Hui Song; Yangyang Wei; Pengtao Li; Quanwei Lu; Nan Hu; Yuling Liu; Yongqing Zhao; Jinrong Liu; Baohong Zhang; Renhai Peng (Food Research International, 2023)

A negative-response strain sensor towards wearable microclimate changes for body area sensing networks - Jing Liu; Junze Zhang; Zeyu Zhao; Yanping Liu; Wai Cheong Tam; Zhaozhu Zheng; Xiaoqin Wang; Yuling Li; Zekun Liu; Yi Li; Gang Li (Chemical Engineering Journal, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

Effect of Nitrification Inhibitor Addition on Rice N Utilization and Soil Bacterial Community - Pengfu Hou; Suya Zhao; Shiying He; Yuling Zhou; Evangelos Petropoulos; Ian Willett; Lihong Xue; Linzhang Yang; Deli Chen (Journal of Soil Science and Plant Nutrition, 2023)

Activated abscisic acid pathway and C4 pathway, inhibited cell cycle progression, responses of Ulva prolifera to short term high temperature elucidated by multi-omics - Hui Zhao; Xuanhong Liu; Ting Jiang; Chuner Cai; Kai Gu; Yuling Liu; Peimin He (Marine Environmental Research, 2023)

Peroxydisulfate activation using Fe, Co co-doped biochar and synergistic effects on tetracycline degradation - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Spatial scale transformation–based estimation model for fresh grass yield: a case study of the Xilingol Grassland, Inner Mongolia, China - Haixin Liu; Anbing Zhang; Yuling Zhao; Anzhou Zhao; Dongli Wang (Environmental Science and Pollution Research, 2023)

Bacterial community structure and diversity in the rhizospheric soil of Robinia pseudoacacia and Juniperus sabina planted in iron tailings matrix - Xiaolin Chen; Haipeng Chen; Jiaqi Zhao; Yue Xin; Yuling Li (Environmental Science and Pollution Research, 2022)

Response of potential activity, abundance and community composition of nitrite‐dependent anaerobic methanotrophs to long‐term fertilization in paddy soils - Yuling Yang; Lidong Shen; Yanan Bai; Xu Zhao; Shuwei Wang; Jiaqi Liu; Xin Liu; Maohui Tian; Wangting Yang; Jinghao Jin; Hechen Huang; Hongsheng Wu (Environmental Microbiology, 2022)
The process of nitrite‐dependent anaerobic methane oxidation (n‐damo) catalysed by Candidatus Methylomirabilis oxyfera ( M . oxyfera )‐like bacteria is a novel pathway in regulating methane (CH 4 ) emissions from paddy fields. Nitrogen fertilization is essential to improve rice yields and soil fertility; however, its effect on the n‐damo process is largely unknown. Here, the potential n‐damo activity, abundance and community composition of M . oxyfera ‐like bacteria were investigated in paddy fields under three long‐term (32 years) fertilization treatments, i.e. unfertilized control (CK), chemical fertilization (NPK) and straw incorporation with chemical fertilization (SNPK). Relative to the CK, both NPK and SNPK treatments significantly ( p M . oxyfera ‐like bacteria. The variation of soil organic carbon (OrgC) content and inorganic nitrogen content caused by the input of chemical fertilizers and straw returning were identified as the key factors affecting the potential n‐damo activity and the abundance of M . oxyfera ‐like bacteria. However, the community composition and diversity of M . oxyfera ‐like bacteria did not change significantly by the input of fertilizers. Overall, our results provide the first evidence that long‐term fertilization greatly stimulates the n‐damo process, indicating its active role in controlling CH 4 emissions from paddy fields.

How rainfalls influence urban traffic congestion and its associated economic losses at present and in future: taking cities in the Beijing-Tianjin-Hebei region, China for example? - Yi Zhou; Sicheng Mao; Haile Zhao; Guoliang Zhang; Xin Chen; Yuling Jin; Lin Xu; Zhihua Pan; Pingli An; Fei Lun (Theoretical and Applied Climatology, 2022)

Synthesis and Luminescent Properties of 1,4,5-Triphenylimidazole‒Phenothiazine Fluorophores - Long Qian; Hongyan Yang; Yuling Zhao; Yongchun Guo; Tianzhi Yu (Journal of Fluorescence, 2022)

Human umbilical cord-derived mesenchymal stem cells ameliorate psoriasis-like dermatitis by suppressing IL-17-producing γδ T cells - Youdong Chen; Yifan Hu; Xue Zhou; Zihan Zhao; Qian Yu; Zeyu Chen; Yuanyuan Wang; Peng Xu; Zengyang Yu; Chunyuan Guo; Xilin Zhang; Yuling Shi (Cell and Tissue Research, 2022)

Analysis of allelic variants of RhMLO genes in rose and functional studies on susceptibility to powdery mildew related to clade V homologs - Peihong Fang; Paul Arens; Xintong Liu; Xin Zhang; Deepika Lakwani; Fabrice Foucher; Jérémy Clotault; Juliane Geike; Helgard Kaufmann; Thomas Debener; Yuling Bai; Zhao Zhang; et al. (Theoretical and Applied Genetics, 2021)
Key message Rose has 19 MLO genes. Of these, RhMLO1 and RhMLO2 were shown to be required for powdery mildew infection, which suggests their potential as susceptibility targets towards disease resistance. Abstract Powdery mildew, caused by Podosphaera pannosa , is one of the most serious and widespread fungal diseases for roses, especially in greenhouse-grown cut roses. It has been shown that certain MLO genes are involved in powdery mildew susceptibility and that loss of function in these genes in various crops leads to broad-spectrum, long-lasting resistance against this fungal disease. For this reason, these MLO genes are called susceptibility genes. We carried out a genome-wide identification of the MLO gene family in the Rosa chinensis genome, and screened for allelic variants among 22 accessions from seven different Rosa species using re-sequencing and transcriptome data. We identified 19 MLO genes in rose, of which four are candidate genes for functional homologs in clade V, which is the clade containing all dicot MLO susceptibility genes. We detected a total of 198 different allelic variants in the set of Rosa species and accessions, corresponding to 5–15 different alleles for each of the genes. Some diploid Rosa species shared alleles with tetraploid rose cultivars, consistent with the notion that diploid species have contributed to the formation of tetraploid roses. Among the four RhMLO genes in clade V, we demonstrated using expression study, virus-induced gene silencing as well as transient RNAi silencing that two of them, RhMLO1 and RhMLO2 , are required for infection by P. pannosa and suggest their potential as susceptibility targets for powdery mildew resistance breeding in rose.

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Meta-analysis of the effect of the overexpression of aquaporin family genes on the drought stress response - Jianhong Ren; Xiaoxiao Yang; Chunying Ma; Yuling Wang; Juan Zhao; Le Kang (Plant Biotechnology Reports, 2021)

Macrophage-Derived Extracellular Vesicles as Drug Delivery Systems for Triple Negative Breast Cancer (TNBC) Therapy - Matthew J. Haney; Yuling Zhao; Yeon S. Jin; Samuel M. Li; Juli R. Bago; Natalia L. Klyachko; Alexander V. Kabanov; Elena V. Batrakova (Journal of Neuroimmune Pharmacology, 2020)

Interleukin-25 in sputum as a marker of airway inflammation in children asthma - Yun Zhang; Cuifen Zhao; Xiuxia Zhao; Qingyu Kong; Mingjie Ding; Yuling Han; Xiang Ma; Lu Cheng (Science China Life Sciences, 2019)

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

MiR-153 regulates cardiomyocyte apoptosis by targeting Nrf2/HO-1 signaling - Xianting Zhu; Yuling Zhao; Wei Hou; Ling Guo (Chromosome Research, 2019)

D-RADA16-RGD-Reinforced Nano-Hydroxyapatite/Polyamide 66 Ternary Biomaterial for Bone Formation - WeiKang Zhao; Bin He; Ao Zhou; Yuling Li; Xiaojun Chen; Qiming Yang; Beike Chen; Bo Qiao; Dianming Jiang (Tissue Engineering and Regenerative Medicine, 2019)

Spatiotemporal Change of Sparse Vegetation Coverage in Northern China - Lili Feng; Zhiqing Jia; Qingxue Li; Anzhou Zhao; Yuling Zhao; Zhaojiang Zhang (Journal of the Indian Society of Remote Sensing, 2019)

Spatiotemporal Change of Aeolian Desertification Land Distribution in Northern China from 2001 to 2015 - Lili Feng; Zhiqing Jia; Qingxue Li; Anzhou Zhao; Zhaojiang Zhang; Yuling Zhao (Journal of the Indian Society of Remote Sensing, 2018)

Synthesis, Characterization and Luminescent Properties of Anthracen- or Pyrene-Based Coumarin Derivatives - Hui Zhang; Li Zhao; Qinglong Luo; Yuling Zhao; Tianzhi Yu (Journal of Fluorescence, 2018)

Response of Vegetation Productivity to Climate Change and Human Activities in the Shaanxi–Gansu–Ningxia Region, China - Haixin Liu; Anbing Zhang; Tao Jiang; Anzhou Zhao; Yuling Zhao; Dongli Wang (Journal of the Indian Society of Remote Sensing, 2018)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Optimization of Lipid Extraction and Determination of Fatty Acid Compositions in Edible Meats of Freshwater and Marine Shrimps - Li Zhou; Peixuan Li; Yuling Zhao; Shuang Hou; Baolei Cong; Jun Huang; Yu Ding; Xiaoxiong Zeng (Journal of Aquatic Food Product Technology, 2017)

Valosin-containing protein (VCP) promotes the growth, invasion, and metastasis of colorectal cancer through activation of STAT3 signaling - Qianfeng Fu; Yuling Jiang; Daxin Zhang; Xiuli Liu; Junfeng Guo; Jinlong Zhao (Molecular and Cellular Biochemistry, 2016)

A New Star-shaped Carbazole Derivative with Polyhedral Oligomeric Silsesquioxane Core: Crystal Structure and Unique Photoluminescence Property - Zixuan Xu; Tianzhi Yu; Yuling Zhao; Hui Zhang; Guoyun Zhao; Jianfeng Li; Lanqin Chai (Journal of Fluorescence, 2016)

Synthesis, Crystal Structures and Photo- and Electro-Luminescence of Copper(I) Complexes Containing Electron-Transporting Diaryl-1,3,4-Oxadiazole - Tianzhi Yu; Peng Liu; Haifang Chai; Jundan Kang; Yuling Zhao; Hui Zhang; Duowang Fan (Journal of Fluorescence, 2014)

Synthesis, Crystal Structure and Photoluminescence of a Cyclometalated Iridium(III) Coumarin Complex - Tianzhi Yu; Chengcheng Zhang; Yuling Zhao; ShaoQiang Guo; Peng Liu; Wentao Li; Duowang Fan (Journal of Fluorescence, 2013)

High-Efficiency Blue Electroluminescence Based on Coumarin Derivative 3-(4-(anthracen-10-yl)phenyl)-benzo[5,6]coumarin - Hui Zhang; Haifang Chai; Tianzhi Yu; Yuling Zhao; Duowang Fan (Journal of Fluorescence, 2012)

Synthesis, Photo- and Electro-Luminescence of 3-Benzoxazol-2-yl-Coumarin Derivatives - Yuling Zhao; Tianzhi Yu; Youzhi Wu; Hui Zhang; Duowang Fan; Zunwei Gan; Liangliang Yang; Xiaoqian Han; Yumei Zhang (Journal of Fluorescence, 2012)

High glucose induced rat aorta vascular smooth muscle cell oxidative injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Yan Zhang; Zhonghong Gao (Journal of Physiology and Biochemistry, 2011)

High glucose induced human umbilical vein endothelial cell injury: involvement of protein tyrosine nitration - Yuling Zhao; Naihao Lu; Hailing Li; Yan Zhang; Zhonghong Gao; Yuefa Gong (Molecular and Cellular Biochemistry, 2008)

Expression, purification and characterization of pectate lyase A from Aspergillus nidulans in Escherichia coli - Qingxin Zhao; Sheng Yuan; Yuling Zhang; Hong Zhu; Chuanchao Dai; Fang Yang; Fengmin Han (World Journal of Microbiology and Biotechnology, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)